MGR, the man and the myth - Mohandas, K. (Bangalore : Panther Publishers, 1992)
Political biography of M.G. Ramachandran, 1917-1987, a former chief minister of Tamil Nadu.
Keywords: Politicians -- India -- Tamil Nadu -- Biography; Tamil Nadu (India) -- Biography